The role of experience in the assessment of pain in others - Modić Stanke, Koraljka; Ružić, Valentina; Petrak, Olivera; Lučanin, Damir; Ivanec, Dragutin (2010)
Person experiencing pain is usually the most competent one to indicate intensity and unpleasantness of the pain he/she is feeling. However, self-reports of pain are not always possible to obtain, so different methods must be used - one of them is assessment of pain experience conducted by another individual, a professional or an outsider. Since experience usually improves individual’s efficacy in a certain field, it would be expected that professionals - who assess pain on daily basis, would be more accurate in such task than outsiders - who have no experience with such assessment. The aim of this study was to investigate whether level of observer's experience with assessment of pain in others affects such assessment accuracy in experimentally induced pain. Observers, 32 students and 31 nurses, watched 6 video-tapes (3 volunteers in 2 different experimentally induced painful situations) and rated pain experience of the person on the tape. Results show no statistically significant difference between two samples ; both samples generally underestimated pain intensity and unpleasantness - indicating that everyday experience with assessment of pain in others does not improve efficacy in that task. Such finding suggests necessity of educational intervention which would enhance assessment accuracy of medical staff. Further studies are needed to investigate possible difference between professionals and outsiders in assessment accuracy of pain experienced in clinical conditions.
Projekt MZOS
ENG